2007
DOI: 10.1128/iai.00991-07
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Regulates CXC Chemokine Production and Neutrophil Recruitment to the Cornea inOnchocerca volvulus/Wolbachia-Induced Keratitis

Abstract: The filarial nematode Onchocerca volvulus is the causative organism of river blindness. Our previous studies demonstrated an essential role for endosymbiotic Wolbachia bacteria in corneal disease, which is characterized by neutrophil infiltration into the corneal stroma and the development of corneal haze. To determine the role of Toll-like receptors (TLRs) in neutrophil recruitment and activation, we injected a soluble extract of O. volvulus containing Wolbachia bacteria into the corneal stromata of C57BL/6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 41 publications
5
32
1
Order By: Relevance
“…We found, as has been demonstrated previously, that neutrophil migration does not require immunization [11]. Filarial antigens and Wolbachia both efficiently induced neutrophil migration into the corneal stroma, independent of the immunization status.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We found, as has been demonstrated previously, that neutrophil migration does not require immunization [11]. Filarial antigens and Wolbachia both efficiently induced neutrophil migration into the corneal stroma, independent of the immunization status.…”
Section: Discussionsupporting
confidence: 69%
“…Homologies to human onchocercal keratitis may only be hypothesized as human corneal samples for the investigation of pathology are scarce for obvious reasons. Previous studies using this murine model of Onchocerca keratitis demonstrated that (1) there is not only a predominant Th2 response, with elevated IL-4, IL-5, IgE, IgG1, and eosinophilia, but also an induction of IFNγ [10]; (2) the presence of endosymbiotic Wolbachia is essential for neutrophil recruitment to the corneal stroma and development of corneal haze [7]; (3) Wolbachia-induced corneal inflammation is TLR2 and MyD88 dependent [11,12]; and (4) dendritic cell activation and IFNγ production are dependent on TLR2, whereas Th2-associated responses (IL-5 production, eosinophil infiltration into the cornea) are TLR2 independent [13]. These findings are consistent with the hypothesis that Wolbachia induce Th1-associated responses and neutrophil recruitment through TLR2/MyD88-dependent responses, whereas Th2 responses are Wolbachia independent and may be induced directly by filarial antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive work on the mechanism of neutrophil influx into the cornea following infection with Onchocerca volvulus has demonstrated the dependence of this influx on multiple factors originating from cells that are resident in and infiltrate the tissue (28,46). The resulting neutrophil influx and activation was then responsible for keratitis and corneal haze (29). It therefore seems likely that the control of neutrophil recruitment and activation either by adaptive CD4 ϩ Th cells (e.g., Th17 cells) or by chemokines secreted by infected epithelial cells will be crucial, and this requires further investigation.…”
Section: Vol 78 2010mentioning
confidence: 99%
“…the activation of macrophages and their subsequent desensitisation by Wolbachia molecules is dependent both on toll-like receptor (tLr)2 and on the adapter protein MyD88 (Gillette-Ferguson et al, 2006;turner et al, 2006). it was established that Wolbachia-induced inflammation is dependent on tLr2 and tLr6, and partially on tLr1, and that the MyD88/Mal signal transduction pathway is mediated by triF and traM (Hise et al, 2007). recently Wolbachia diacyl lipoproteins were identified as being responsible for tLr2 and tLr6 activation and being involved in proinflammatory cytokine production (turner et al, 2009). current therapeutic approach With antibiotic treatments targeting Wolbachia in the last ten years, investigators have emphasized the association between Wolbachia and filariae and have suggested that the Wolbachia bacteria could provide a novel target for antibiotic-based therapy or a novel antisymbiotic chemotherapy.…”
Section: Wolbachia In Filariaementioning
confidence: 99%